tính : 17\5 x 15\34
giải chi tiết hộ mình nhé
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
$#Shả$
`A)=5/17xx(15/34+19/34)`
`=5/17xx1=5/17`
`B)=(13/12+7/12)+1/3`
`=5/3+1/3=2`
1035 + 207 x 4 x 28 - 69 x 3 x 17
1035 + 207 x 112 - 207 x 17
1035 + 207 x(112-17)
207 x 5 + 207 x 95
207 x (5+95)
\(\frac{17}{2}-\left|2x-\frac{5}{2}\right|=-\frac{7}{6}\)
\(\left|2x-\frac{5}{2}\right|=\frac{17}{2}-\frac{-7}{6}\)
\(\left|2x-\frac{5}{2}\right|=\frac{51}{6}+\frac{7}{6}\)
\(\left|2x-\frac{5}{2}\right|=\frac{29}{3}\)
\(2x-\frac{5}{2}=\frac{29}{3}\)hoặc \(2x-\frac{5}{2}=\frac{-29}{3}\)
Trường hợp 1:
\(2x-\frac{5}{2}=\frac{29}{3}\)
\(2x=\frac{29}{3}+\frac{5}{2}\)
\(2x=\frac{73}{6}\)
\(x=\frac{73}{6}:2\)
\(x=\frac{73}{12}\)
Trường hợp 2:
\(2x-\frac{5}{2}=\frac{-29}{3}\)
\(2x=\frac{-29}{3}+\frac{5}{2}\)
\(2x=\frac{-43}{6}\)
\(x=\frac{-43}{6}:2\)
\(x=\frac{-43}{12}\)
Vậy \(x=\frac{73}{12}\)hoặc \(x=\frac{-43}{12}\)
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12 + 13 + 14 + 15 + 16 + 17+18 = 171 nhé
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12 + 13 + 14 + 15 + 16 + 17+18. = 171
(37-17).(-5)+23.(-13-17)
a, \(\sqrt{15}+\sqrt{8}< \sqrt{16}+\sqrt{9}=4+3=7\)
\(\Rightarrow\sqrt{15}+\sqrt{8}< 7\)
b, \(\sqrt{10}+\sqrt{17}+1>\sqrt{9}+\sqrt{16}+1=3+4+1=8\)
\(\sqrt{61}< \sqrt{64}=8\)
\(\Rightarrow\sqrt{10}+\sqrt{17}+1>\sqrt{61}\)
c, \(\sqrt{10}+\sqrt{5}+1>\sqrt{9}+\sqrt{4}+1=3+2+1=6\)
\(\sqrt{35}< \sqrt{36}=6\)
\(\Rightarrow\sqrt{10}+\sqrt{5}+1>\sqrt{35}\)
\(\frac{17}{13}-\frac{14}{23}+\frac{75}{100}+\frac{9}{13}-\frac{9}{23}+\frac{15}{60}\)
\(=\left(\frac{17}{13}+\frac{9}{13}\right)-\left(\frac{14}{23}+\frac{9}{23}\right)+\left(\frac{75}{100}+\frac{15}{60}\right)\)
\(=\frac{26}{13}-\frac{23}{23}+\left(\frac{3}{4}+\frac{1}{4}\right)\)
\(=2-1+\frac{4}{4}\)
\(=2-1+1\)
\(=2\)
Chúc bạn học tốt
22,
1, Đặt √(3-√5) = A
=> √2A=√(6-2√5)
=> √2A=√(5-2√5+1)
=> √2A=|√5 -1|
=> A=\(\dfrac{\sqrt{5}-1}{\text{√2}}\)
=> A= \(\dfrac{\sqrt{10}-\sqrt{2}}{2}\)
2, Đặt √(7+3√5) = B
=> √2B=√(14+6√5)
=> √2B=√(9+2√45+5)
=> √2B=|3+√5|
=> B= \(\dfrac{3+\sqrt{5}}{\sqrt{2}}\)
=> B= \(\dfrac{3\sqrt{2}+\sqrt{10}}{2}\)
3,
Đặt √(9+√17) - √(9-√17) -\(\sqrt{2}\)=C
=> √2C=√(18+2√17) - √(18-2√17) -\(2\)
=> √2C=√(17+2√17+1) - √(17-2√17+1) -\(2\)
=> √2C=√17+1- √17+1 -\(2\)
=> √2C=0
=> C=0
26,
|3-2x|=2\(\sqrt{5}\)
TH1: 3-2x ≥ 0 ⇔ x≤\(\dfrac{-3}{2}\)
3-2x=2\(\sqrt{5}\)
-2x=2\(\sqrt{5}\) -3
x=\(\dfrac{3-2\sqrt{5}}{2}\) (KTMĐK)
TH2: 3-2x < 0 ⇔ x>\(\dfrac{-3}{2}\)
3-2x=-2\(\sqrt{5}\)
-2x=-2√5 -3
x=\(\dfrac{3+2\sqrt{5}}{2}\) (TMĐK)
Vậy x=\(\dfrac{3+2\sqrt{5}}{2}\)
2, \(\sqrt{x^2}\)=12 ⇔ |x|=12 ⇔ x=12, -12
3, \(\sqrt{x^2-2x+1}\)=7
⇔ |x-1|=7
TH1: x-1≥0 ⇔ x≥1
x-1=7 ⇔ x=8 (TMĐK)
TH2: x-1<0 ⇔ x<1
x-1=-7 ⇔ x=-6 (TMĐK)
Vậy x=8, -6
4, \(\sqrt{\left(x-1\right)^2}\)=x+3
⇔ |x-1|=x+3
TH1: x-1≥0 ⇔ x≥1
x-1=x+3 ⇔ 0x=4 (KTM)
TH2: x-1<0 ⇔ x<1
x-1=-x-3 ⇔ 2x=-2 ⇔x=-1 (TMĐK)
Vậy x=-1
a) \(\dfrac{2}{9}+\dfrac{3}{5}-\dfrac{1}{15}=\dfrac{37}{45}-\dfrac{1}{15}=\dfrac{37}{45}-\dfrac{3}{45}=\dfrac{34}{45}\)
b) \(\dfrac{5}{12}\times\dfrac{4}{5}\div4=\dfrac{1}{3}\div4=\dfrac{1}{12}\)
c) \(\dfrac{8}{9}-\dfrac{4}{15}\div\dfrac{2}{5}=\dfrac{8}{9}-\dfrac{2}{3}=\dfrac{8}{9}-\dfrac{6}{9}=\dfrac{2}{9}\)
Tính
\(\dfrac{17}{5}\times\dfrac{15}{34}\)
\(=\dfrac{1}{1}\times\dfrac{3}{2}=\dfrac{3}{2}\)